Armenia country gender assessment. ([Manila] Asian Development Bank, 2019)
Discusses gender equality concerns in Armenias government, economy, society, and culture. It analyzes gender issues in key sectors such as energy, transport, water supply and municipal services, and entrepreneurship.
Keywords: Women -- Armenia (Republic) -- Social conditions; Women -- Armenia (Republic) -- Economic conditions; Women in development -- Armenia (Republic).; Electronic books